Megahertz serial crystallography - Wiedorn, Max O; Oberthür, Dominik; Bean, Richard; Schubert, Robin; Werner, Nadine; Abbey, Brian; Aepfelbacher, Martin; Adriano, Luigi; Allahgholi, Aschkan; Al-Qudami, Nasser; Andreasson, Jakob; Aplin, Steve; et al. (Nature communications, 2018)
The new European X-ray Free-Electron Laser is the first X-ray free-electron laser capable of delivering X-ray pulses with a megahertz inter-pulse spacing, more than four orders of magnitude higher than previously possible. However, to date, it has been unclear whether it would indeed be possible to measure high-quality diffraction data at megahertz pulse repetition rates. Here, we show that high-quality structures can indeed be obtained using currently available operating conditions at the European XFEL. We present two complete data sets, one from the well-known model system lysozyme and the other from a so far unknown complex of a β-lactamase from K. pneumoniae involved in antibiotic resistance. This result opens up megahertz serial femtosecond crystallography (SFX) as a tool for reliable structure determination, substrate screening and the efficient measurement of the evolution and dynamics of molecular structures using megahertz repetition rate pulses available at this new class of X-ray laser source.